Determinant Government Ownership Structure and Supply Chain Management on Company Performance: Indonesian Public Listed Companies - Hamdi Agustin; Eva Sundari; Yusrawati Yusrawati (International Journal of Supply Chain Management, 2020)
Abstract- The government’s supply chain management (SCM) system is not adequately implemented in state-owned enterprises (SOEs). There are weaknesses in the SOEs SCM enablers, strategies, policy implementation and poor enforcement of government SCM rules and regulations. This purpose of this study to determinant between government ownership (GOV), insider ownership (INSIDER) and bank dummy (Dbank) on company financial performance. In this study, financial performance is measured by return on equity (ROE). The population and sample consists of 20 government companies in Indonesian Public Listed. The period of this study is from 2013 to 2017. The results showed the GOV and INSIDER variables have an effect on ROE while the Dbank variable does not affect the company's financial performance. GOV negative influence on ROE. This shows government political motives. In addition, government-owned companies may have lower profits because they finance a project that does not bring financial gain but brings social benefits. INSIDER positive influence on ROE. This shows managerial ownership will encourage management to improve company performance, because they also have a company.